Teaching Disability Studies in Undergraduate Psychology Programs: Common Themes and Gaps - Madyaningrum, Monica Eviandaru (The Center for Disability Studies and Services Brawijaya University, 2025)
Psychology has been criticized for its tendency to personalize disability issues that have reinforced the stigmatization of people with disabilities as inferior individuals. In response to these critics, there has been a call for integrating the social model of disability into psychological studies and teaching. Against this background, the current study aimed to explore disability teaching in undergraduate programs of psychology at some universities in Indonesia. More specifically, the study wanted to identify the common focus and gap in disability teaching and the extent to which social model of disabilities have been integrated into the existing teaching practices. The orienting questions of this study included: how disability has been generally taught, through what kind of subjects, and what areas of teaching have been less developed. The study employed a qualitative methodology and involved six participants, who are lecturers of undergraduate psychology programs. Data collection was conducted by using semi-structured interviews and analyzed by using inductive thematic analysis. The findings of this study suggested three themes that represented two common focuses and a gap in disability teaching. These include: 1) focusing on disability as a special need, 2) people with disabilities as the focus of interventions, and 3) social model of disability as an underdeveloped area of teaching.